Brain functional training: a perspective article - Da Silva-Grigoletto, Marzo Edir; Pereira-Monteiro, Marcos Raphael; Aragão-Santos, José Carlos; Vasconcelos, Alan Bruno Silva; Marcos-Pardo, Pablo Jorge; Fortes, Leonardo de Sousa (Frontiers in Aging, 2024)
Introduction: Physical exercise (PE) positively affects the nervous system, impacting morphology and physiology. It increases brain gray and white matter, improves cerebral blood flow, and stimulates neurogenesis, synaptogenesis, and angiogenesis, promoting brain function. Although exercise already affects cognition, some training modalities place greater demands on the cognitive aspects of physical exercise, such as perceptual-motor and visual-motor training. This type of approach aims to emphasize the cognitive adaptations that occur chronically. Specifically for older people, functional training, a multi-component approach, is a promising exercise modality that stimulates functionality using multi-joint, multi-planar exercises mirroring daily activities. However, applying a greater focus on cognitive adaptations in line with the functional training proposal for maximal benefits remains underexplored.Aim: Thus, this perspective article initially explores different exercise approaches emphasizing cognitive adaptations and proposes Brain Functional Training to improve older adult’s functionality.Methods: Furthermore, we explain how brain functional training can be explored to emphasize cognitive aspects based on increasing complexity to stimulate the executive function and its subdomains.Conclusion: This proposal is one alternative to combining motor and cognitive stimuli to promote autonomy and health in older people.